2017
DOI: 10.1097/md.0000000000006263
|View full text |Cite
|
Sign up to set email alerts
|

Neovascular glaucoma after vitrectomy in patients with proliferative diabetic retinopathy

Abstract: To evaluate the prevalence and risk factors of neovascular glaucoma (NVG) after vitrectomy in patients with vitreous hemorrhage associated with proliferative diabetic retinopathy (PDR). This retrospective, noncomparative, observational study included 127 eyes of 127 patients with PDR who received vitrectomy with a follow-up period of at least 6 months. The prevalence of NVG and associated risk factors were assessed including sex, age, previous panretinal photocoagulation, baseline intraocular pressure, combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
2
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 61 publications
3
30
2
5
Order By: Relevance
“…The early anterior chamber angle does not adhere to form open-angle glaucoma, whereas late anterior chamber angle adhesion forms open-angle glaucoma (also termed refractory glaucoma). 1 Studies have shown that the average incidence of NVG is 6.6/10,000 patients (0.66%). In the Asian population, NVG accounts for 0.7-5.1% of glaucoma cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early anterior chamber angle does not adhere to form open-angle glaucoma, whereas late anterior chamber angle adhesion forms open-angle glaucoma (also termed refractory glaucoma). 1 Studies have shown that the average incidence of NVG is 6.6/10,000 patients (0.66%). In the Asian population, NVG accounts for 0.7-5.1% of glaucoma cases.…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences in spontaneous brain activity between the NVG group and HCs in the right regions. Notes: The different brain regions were observed in the left precuneus (3), bilateral cuneus (2), bilateral middle frontal gyrus(1). The yellow areas denote lower FC brain regions, and the red areas denote higher FC brain regions.…”
mentioning
confidence: 99%
“…При этом развитие послеоперационных осложнений отмечают и сторонники комбинированного подхода к хирургическому лечению данной категории больных, акцентируя внимание на необходимости проведения более масштабных исследований для определения наиболее безопасных сроков выполнения ФЭК [36][37][38]. Так, в ретроспективном исследовании Qin-Xiang Zheng et al (2010) отметили, что наиболее распространенным изменением переднего отрезка в послеоперационном периоде является фиброз задней капсулы хрусталика, который развивается в 17,5 % случаев [37].…”
unclassified
“…При этом назначение медикаментозного гипотензивного режима часто бывает недостаточно эффективным в лечении НВГ, что обусловливает необходимость проведения дополнительного оперативного вмешательства. Jin-woo Kwon et al (2017) показали, что НВГ развилась в 11,8 % случаев у пациентов с ПДР после выполнения факовитрэктомии, а у 46,6 % из них потребовалось проведение дополнительной хирургии -антиглаукомной операции с имплантацией ахмед-дренажа [36].…”
unclassified
See 1 more Smart Citation